2017
DOI: 10.1016/j.carbpol.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer assembled hydrophobic coatings for cellulose nanofibril films and textiles, made of polylysine and natural wax particles

Abstract: PDF/A is an ISO-standardized version of the Portable Document Format (PDF) specialized for the digital preservation of electronic documents. The extension in the file name is pdf. PDF/A differs from "normal" PDF in that features ill-suited for long-term archiving are omitted. PDF/A embeds all fonts used in the document within the PDF file, so that the user of your file will not have to have the same fonts that you used to create the file installed on their computer in order to read it. Recommended versions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 65 publications
4
55
0
Order By: Relevance
“…technical textile applications. 138 The possibility to apply particulate coating from aqueous dispersion of spherical lignin particles cuts off the emission of volatile organic compounds (VOCs), contributing to the waste prevention goal.…”
Section: Coatings and Paintsmentioning
confidence: 99%
“…technical textile applications. 138 The possibility to apply particulate coating from aqueous dispersion of spherical lignin particles cuts off the emission of volatile organic compounds (VOCs), contributing to the waste prevention goal.…”
Section: Coatings and Paintsmentioning
confidence: 99%
“…Hydrophobization by wax coatings has gained scientific interest, and to overcome the lack of breathability of solid wax films, different ways of producing colloidal wax particles have been recently reported (Lozhechnikova, Bellanger, Michen, Burgert, & Österberg, 2017;Morrissette et al, 2018;Wang, Qian, & Shen, 2018). However, so far very few of the methods utilize solely wax and water without any surfactants and other solvents and the scalability of the methods have not been thoroughly assessed (Forsman et al, 2017;Lozhechnikova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CW-treated wood has been shown to have a water contact angle to be higher than 120 • , as well as improved moisture buffering based on noncontinuous coating of CW particles [27]. The wax film is durable, and consecutive thermal treatment leads to melting of the wax particles, even causing no decrease in the hydrophobicity [28]. It can be concluded that wood coated with a CW emulsion may repel water well.…”
mentioning
confidence: 99%